Can schools reduce bullying? The relationship between school characteristics and the prevalence of bullying behaviours. (21st February 2017) - Muijs, Daniel
Abstract : Background: Bullying remains a persistent phenomenon in schools, but the extent to which day‐to‐day policies and practices relate to bullying prevalence has not been widely studied. In this study, we use an educational effectiveness framework to interrogate this relationship. Aims: The aim was to study the relationship between school factors and prevalence of bullying in primary schools. We hypothesize that school conditions (e.g., size), school policies (e.g., behaviour policies), and school processes (e.g., teaching quality) are related to bullying prevalence. Sample: Surveys were administered to pupils in 35 primary schools in four local authorities in England. Pupils ( N  = 1, 411) and teachers ( N  = 68) in the final year of primary school (year 6) were surveyed. Methods: This study drew on the following data sources: A pupil survey on bullying behaviours A survey of teachers on school policies and processes Analysis of data on school processes from school inspection reports Analysis of secondary data on school conditions and pupil characteristics. Three‐level multilevel models were used to analyse the data. Results: Results show a substantial school‐ and classroom‐level effect on prevalence of bullying. Effective school policies were found to be related to levels of bullying. Conclusions: The study provides support for the importance of schools' embedded policies and practices in relation to bullying prevalence and provides evidence for policy on the importance of focusing on a broad range of outcomes.